أثر الضرائب في الاستهلاك في سورية بين عامي 2000-2010 (دراسة تحليلية) - العماّر, رضوان وليد; درويش, هنادي سليمان (Latakia University Journal - Economic and Legal Sciences Series, 2016)
تناول هذا البحث دراسة استخدام الضرائب في سورية كأداة هامة في التأثير في إحدى المتغيرات الاقتصادية الهامة(الاستهلاك) بين عامي (2000-2010)،كأن تُستخدم هذه الضرائب والرسوم مثلاً لدعم زيادة استهلاك بعض السلع التي تعتبر سلعاً أساسية وضرورية أو لمحاولة الحد من حجم استهلاك سلع أخرى كالكماليات. قام المشرع السوري خلال الفترة المدروسة بإجراء تعديلات ضريبية عدة (وخاصة رسم الإنفاق الاستهلاكي) للتأثير في حجم الاستهلاك المحلي، إن كان استهلاكاً عاماً أو استهلاكاً خاصاً، فكان هناك تعديل كبير في معدلات بعض الضرائب المباشرة إلى جانب التوسع في قاعدة السلع والخدمات التي تم إخضاعها لبعض أنواع الضرائب غير المباشرة، ومنها لرسم الإنفاق الاستهلاكي حيث امتد إلى بعض السلع الضرورية . This research studied the use of taxes in Syria as an important tool in influencing one of the variables important economic (consumption) between the years (2000-2010). These taxes and fees are used (for example) to support an increase in the consumption of some goods that are considered commodities and necessary, or to try to reduce the amount of consumption of luxury goods. The Syrian legislator made during the period studied adjustments numerous tax (especially fee consumer spending) to influence the amount of the domestic consumption, for the consuming public or consuming particular. There was a major adjustment in tax rates of some of the direct taxes and the expansion of the base of goods and services that are subject to certain types of indirect taxes, and to draw them where consumer spending has spread to some of the essential commodities.